2011
DOI: 10.1093/aje/kwr027
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phospholipid Fatty Acids and Prostate Cancer Risk: Results From the Prostate Cancer Prevention Trial

Abstract: Inflammation may be involved in prostate cancer development and progression. This study examined the associations between inflammation-related phospholipid fatty acids and the 7-year-period prevalence of prostate cancer in a nested case-control analysis of participants, aged 55-84 years, in the Prostate Cancer Prevention Trial during 1994-2003. Cases (n = 1,658) were frequency matched to controls (n = 1,803) on age, treatment, and prostate cancer family history. Phospholipid fatty acids were extracted from ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
4
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 34 publications
7
131
4
4
Order By: Relevance
“…No significant associations were found between individual blood levels of EPA or DHA and total prostate cancer risk, risk of advanced prostate cancer, or risk of highgrade prostate cancer. In a further analysis, the authors combined the results obtained for DHA and for EPA individually and found a positive association in this combined analysis of EPA and DHA and risk of high-grade prostate cancer (pooled RR = 1.39, 95 % CI = 1.07-1.80; p = 0.021; I 2 = 17.6 %, p = 0.291), based on one case-control and three nested case-control studies (Crowe et al, 2008;Park et al, 2009;Shannon et al, 2010;Brasky et al, 2011). However, the Panel notes that there is no rationale for combining the results obtained for DHA and for EPA individually in a pooled estimate.…”
Section: Nested Case-control and Case-control Studies On Blood Biomarmentioning
confidence: 80%
See 1 more Smart Citation
“…No significant associations were found between individual blood levels of EPA or DHA and total prostate cancer risk, risk of advanced prostate cancer, or risk of highgrade prostate cancer. In a further analysis, the authors combined the results obtained for DHA and for EPA individually and found a positive association in this combined analysis of EPA and DHA and risk of high-grade prostate cancer (pooled RR = 1.39, 95 % CI = 1.07-1.80; p = 0.021; I 2 = 17.6 %, p = 0.291), based on one case-control and three nested case-control studies (Crowe et al, 2008;Park et al, 2009;Shannon et al, 2010;Brasky et al, 2011). However, the Panel notes that there is no rationale for combining the results obtained for DHA and for EPA individually in a pooled estimate.…”
Section: Nested Case-control and Case-control Studies On Blood Biomarmentioning
confidence: 80%
“…Considering the individual results of available nested case-control studies which looked at DHA alone and total prostate cancer risk, three reported a positive association (Crowe et al, 2008;Brasky et al, 2011;Brasky et al, 2013), three found no significant association (Harvei et al, 1997;Mannisto et al, 2003;Park et al, 2009) and two found a negative association (Norrish et al, 1999;Chavarro et al, 2007); no significant association was found in the five available case-control studies (Godley et al, 1996;Newcomer et al, 2001;Ukoli et al, 2009;Shannon et al, 2010;Ukoli et al, 2010). With respect to DHA and low-or high-grade prostate cancer risk, one nested case-control study reported a positive association for low-but not high-grade prostate cancer (Brasky et al, 2013), while another nested case-control study reported opposite findings (Brasky et al, 2011); three nestedcase control (Chavarro et al, 2007;Crowe et al, 2008;Park et al, 2009) and one case-control study (Shannon et al, 2010) found no significant association with either low-or high-grade prostate cancer. Overall, the Panel notes that results from studies on an association between blood biomarkers of DHA and EPA and prostate cancer risk are inconsistent, with a majority of nested case-control and casecontrol studies finding null or negative associations.…”
Section: Nested Case-control and Case-control Studies On Blood Biomarmentioning
confidence: 99%
“…[33][34][35][36][37][38] All studies uniformly compared prostate cancer risk with the groups of involved population with the highest blood level of long chain n-3 PUFA and the reference group (lowest blood level). Most studies analyzed risk of prostate cancer development as part of their studies' outcome.…”
Section: Resultsmentioning
confidence: 99%
“…28,[35][36][37] Five studies included high-grade tumour (defined as tumour Gleason score ≥7) in their analysis of outcome. 30,[35][36][37][38] The age range of the study population was 40 to 86 years old. Overall, we analyzed 4516 prostate cancer cases and 5728 matching controls.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have associated n-3 LC-PUFA status with prostate cancer (Brasky et al, 2011(Brasky et al, , 2013. The interpretation of these data has been criticized on a number of grounds including the fact that n-3 LC-PUFA intake was not monitored in these studies and, as n-3 LC-PUFA supplementation is not uncommon in cancer patients (see above), the reason for the observed association between n-3 LC-PUFA and prostate cancer cannot be established.…”
Section: Negative Reportsmentioning
confidence: 99%